Differential potency of vitamin D3, folic acid and memantine in protecting against neurobehavioral alterations of scopolamine induced Alzheimer’s model in rats - Eldeeb, Abeer A.; Fathy, Amira E.; Elgendy, Salwa A. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Alzheimer disease is the cause of 60% to 70% of cases of dementia in elderly people, it is a chronic neurodegenerative disease that usually starts slowly and worsens over time. AD is characterized by the presence of senile plaques enriched with insoluble aggregate of beta-amyloid, neurofibrillary tangles and cholinergic neuronal degeneration in the brain tissue, leading to neural dysfunction, neuroinflammation, and critical pathological perturbations. Methods: Thirty-six males were classified into control group, Alzheimer-induced model (scopolamine 2.5 mg/kg IP once daily for 21 days). Folic acid-treated group (4 mg/kg, IP) once daily for 21 days with scopolamine. Vitamin D3-treated group (42 IU/kg, SC) once daily for 21 days with scopolamine. Vitamin D3 and folic acid-treated group (vitamin D3; 42 IU/kg, SC and folic acid; 4 mg/kg, IP) once daily with scopolamine for 21 days. Memantine-treated group (20 mg/kg IP) once daily with scopolamine for 21 days. Results: Induction of Alzheimer’s showed significant decrease in brain tissue levels of BDNF, Ach, glutathione reductase and significant increase in amyloid peptide 1-42 level with significant memory impairment, significant increase of initial acquisition latency, firstt retention latency and second retention latency. While administration of folic acid, vitamin D3, memantine separately or in combination resulted insignificant increase of brain tissue levels of BDNF, Ach, glutathione reductase with significant reduction of amyloid peptide 1-42 level with significant memory improvement (significant decrease IAL, first RL and second RL). Also showed improvement of histopathological changes occurred in the brain. Conclusions: Data obtained in the present study revealed that treatment of experimentally induced alzheimer rats with folic acid or vitamin D3 or memantine separately or combined group (folic acid+vitamin D3) resulted in significant increase of brain tissue levels of BDNF, acetyl choline, glutathione reductase with significant reduction of amyloid peptide 1-42 level with significant decrease of IAL, first RL and second RL to reach the platform with improvement of histopathological changes occurred in the brain. But combined and memantine-treated groups resulted in more significant improvement than other treated groups.